(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Robotic-assisted total knee arthroplasty (RA-TKA) has been increasingly adopted with the aim of improving surgical precision, implant alignment, and soft-tissue balancing. These technical advantages are hypothesized to enhance early postoperative functional recovery and patient satisfaction when compared with conventional total knee arthroplasty (C-TKA). However, prospective single-center data evaluating these early outcomes remain limited. Objective: To compare early functional outcomes and patient satisfaction between robotic-assisted and conventional total knee arthroplasty in a prospective single-center cohort. Methods: This prospective observational study was conducted at a single tertiary care center between September 2024 and September 2025. A total of 90 patients undergoing primary unilateral total knee arthroplasty for end-stage osteoarthritis were included, with 45 patients undergoing RA-TKA and 45 undergoing C-TKA. Functional outcomes were assessed using the Knee Society Score (KSS – function) and KOOS JR at 6 weeks and 3 months postoperatively. Patient satisfaction was evaluated at 3 months using a standardized 5-point Likert scale. Secondary outcome measures included operative time, length of hospital stay, early postoperative complications, and radiographic alignment accuracy, with alignment outliers defined as a deviation greater than 3° from the neutral mechanical axis. Statistical analysis was performed using appropriate parametric and non-parametric tests, with statistical significance set at p<0.05. Results: Baseline demographic characteristics and preoperative functional scores were comparable between the two groups. Patients in the RA-TKA group demonstrated significantly higher KSS-function and KOOS JR scores at both 6 weeks and 3 months compared with those in the C-TKA group (p<0.05). At 3 months, a greater proportion of patients in the RA-TKA group reported being “very satisfied” with their surgical outcome compared with the C-TKA group (71.1% vs 51.1%; p=0.048). Radiographic alignment outliers were significantly fewer in the RA-TKA group (6.7% vs 20.0%; p=0.041). Operative time was longer in the RA-TKA group, while length of hospital stay and early complication rates were similar between groups. Conclusion: Robotic-assisted total knee arthroplasty is associated with superior early functional outcomes, improved patient satisfaction, and more accurate limb alignment compared with conventional total knee arthroplasty, albeit with increased operative time.